Analysis Of The Quality Of Fresh Fruit Bunches (FFB) Of Oil Palm Received Using The Seven Tools And FMEA Methods (Case Study At Pt Sawit Inti Raya) - Reyhan Islami; Nursya’bani Purnama (International Journal of Economics, Business and Innovation Research, 2025)
PT. Sawit Inti Raya is engaged in palm oil processing. This company was established because of the large potential market for palm oil processing and the large number of palm oil farmers in Riau. However, in recent times, PT. Sawit Inti Raya has faced a complex problem. The problem is the large number of damaged fresh fruit bunches provided by palm oil farmers and received by the company. The extent to which quality control in PT. Sawit Inti Raya's production is assessed in this study, the Seven Quality Control method is used. The data used in this study came from rejected products from February, March, and April 2024. At PT. Sawit Inti Raya, the highest level of defective products was caused by environmental conditions, overripe and damaged fruit bunches, and pests. The results of the study indicate that the most important improvements must be made. First, farmers must be trained in the correct FFB harvesting techniques, use monitoring tools, conduct regular inspections and use of pesticides, and monitor and adjust harvesting methods.